Effects of exercise therapy on patients with poststroke cognitive impairment: A systematic review and meta-analysis - Zhang, Yuanxing; Qiu, Xichenhui; Chen, Jinghao; Ji, Cuiling; Wang, Fang; Song, Dan; Liu, Caiyan; Chen, Lu; Yuan, Ping (Frontiers in Neuroscience, 2023)
Objective: To evaluate the effects of exercise therapy on patients with post-stroke cognitive impairment and to compare the effect differences between this method and conventional measures, providing evidence for a more standardized and effective clinical application of exercise therapy. Methods: 7 electronic databases, such as PubMed, CINAHL, Web of Science, CENTRAL, CNKI, Wanfang, SinoMed and clinical trials registry platforms were searched for randomized controlled trials about exercise therapy on patients with post-stroke cognitive impairment from inception until January 2023. 2 researchers independently screened the literature, evaluated the quality and extracted information. Meta-analysis was implemented with Review Manager 5.4 software. Results: 11 studies involving 1,382 patients were included. Meta-analysis showed that exercise therapy could improve cognitive function [SMD = 0.67, 95%CI(0.31, 1.04), P = 0.0003], motor function [SMD = 1.81, 95%CI(0.41, 3.20), P = 0.01] and activities of daily living [MD = 8.11, 95%CI(3.07, 13.16), P = 0.002] in patients with post-stroke cognitive impairment. Conclusion: Exercise therapy can not only improve cognitive function in patients with post-stroke cognitive impairment, but also improve motor function and activities of daily living. Medical staff should attach importance to the management of patients with post-stroke cognitive impairment and carry out exercise therapy actively, in order to improve the cognitive function of stroke patients. Systematic review registration: https://www.crd.york.ac.uk/prospero/ identifier: CRD42023397553.